Non-invasive early detection of cancer four years before conventional diagnosis using a blood test - Chen, Xingdong; Gole, Jeffrey; Gore, Athurva; He, Qiye; Lu, Ming; Min, Jun; Yuan, Ziyu; Yang, Xiaorong; Jiang, Yanfeng; Zhang, Tiejun; Suo, Chen; Li, Xiaojie; et al. (Nature communications, 2020)
Early detection has the potential to reduce cancer mortality, but an effective screening test must demonstrate asymptomatic cancer detection years before conventional diagnosis in a longitudinal study. In the Taizhou Longitudinal Study (TZL), 123,115 healthy subjects provided plasma samples for long-term storage and were then monitored for cancer occurrence. Here we report the preliminary results of PanSeer, a noninvasive blood test based on circulating tumor DNA methylation, on TZL plasma samples from 605 asymptomatic individuals, 191 of whom were later diagnosed with stomach, esophageal, colorectal, lung or liver cancer within four years of blood draw. We also assay plasma samples from an additional 223 cancer patients, plus 200 primary tumor and normal tissues. We show that PanSeer detects five common types of cancer in 88% (95% CI: 80–93%) of post-diagnosis patients with a specificity of 96% (95% CI: 93–98%), We also demonstrate that PanSeer detects cancer in 95% (95% CI: 89–98%) of asymptomatic individuals who were later diagnosed, though future longitudinal studies are required to confirm this result. These results demonstrate that cancer can be non-invasively detected up to four years before current standard of care. Patients whose disease is diagnosed in its early stages have better outcomes. In this study, the authors develop a non invasive blood test based on circulating tumor DNA methylation that can potentially detect cancer occurrence even in asymptomatic patients.